Publicness as an architectural value - Spector, Tom (Journal of Architecture and Urbanism, 2014)
That architecture should in some way serve the public good is an idea that mostly goes unquestioned. The corresponding idea that we know who the public is and what its good consists of largely falls apart in the face of even a little probing. This paper investigates the concept of the public inherited from the Enlightenment, its fate in recent times, and possibilities for its reinvention. The argument then goes on to suggest ways in which architecture can have relatively more or less of the quality of publicness.